Pressure drop and friction factor for different shapes of microchannels - Gunnasegaran P.; Mohammed H.; Shuaib N.H. (2023)
A numerical investigation has been performed on the pressure drop and friction factor of water flow in three different shapes of microchannel heat sinks which are rectangular, trapezoidal, and triangular for Reynolds number range of 100-1000. The three-dimensional steady, laminar flow and heat transfer governing equations are solved using the finite volume method. It is found that the values of Poiseuille number and friction factor depend greatly on different geometrical parameters. It is also inferred that the heat sink having the smallest hydraulic diameter for each type of shapes under consideration has better performance among the other heat sinks studied. The values of Poiseuille number and friction factor increase with the increase of width-height ratio (Wc/Hc) for rectangular microchannels. For trapezoidal microchannels, the Poiseuille number and friction factor increase with the increase of bottom-to-top width ratio (b/a), increase with the decrease of height-to-top width ratio (h/a), increase with the decrease of length-tohydraulic diameter ratio (L/Dh). While for triangular microchannels, the Poiseuille number and friction factor increase with the increase of its tip angle (?). It is identified that the transition Reynolds number from laminar flow to turbulent flow is occurred at 1100. 2009 IEEE.